2020
DOI: 10.1111/bcp.14697
|View full text |Cite
|
Sign up to set email alerts
|

Effect of capmatinib on the pharmacokinetics of digoxin and rosuvastatin administered as a 2‐drug cocktail in patients with MET‐dysregulated advanced solid tumours: A phase I, multicentre, open‐label, single‐sequence drug–drug interaction study

Abstract: Aims Capmatinib, an orally bioavailable, highly potent and selective MET inhibitor, was recently approved to treat adult patients with metastatic nonsmall cell lung cancer with METex14 skipping mutations. The study investigated the effect of capmatinib on the pharmacokinetics of a single oral dose of digoxin and rosuvastatin in patients with MET‐dysregulated advanced solid tumours. Methods This was a multicentre, open‐label, single‐sequence study. An oral drug cocktail containing 0.25 mg digoxin and 10 mg rosu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 37 publications
(87 reference statements)
1
14
0
Order By: Relevance
“…The safety of capmatinib was consistent with previously reported data 17,25,26 . Capmatinib demonstrated a manageable toxicity profile in this population of 37 patients with MET ‐dysregulated advanced solid tumours.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The safety of capmatinib was consistent with previously reported data 17,25,26 . Capmatinib demonstrated a manageable toxicity profile in this population of 37 patients with MET ‐dysregulated advanced solid tumours.…”
Section: Discussionsupporting
confidence: 89%
“…However, when the effect of capmatinib on CYP3A TDI was assessed using human hepatocytes suspended in plasma, no CYP3A TDI was observed. We have previously shown that capmatinib is an inhibitor and a substrate of P‐gp 17 . It is possible that the P‐gp dependent efflux could limit the entry into the hepatocytes, with less access to the enzymes, thus lowering the metabolism and also the inhibition potential.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because the distribution phases for both compounds end well before that. 15,16 Given the well-understood PK of these compounds, 30 hours of monitoring provides exposure estimates of sufficient accuracy to quantify and categorize the magnitude of the drug interaction(s) and make reasonable dosing recommendations. Second, due to the progressive nature of the disease, and patients' rapidly increasing morbidity over time, crossover study design with multiple periods and intercurrent washouts is not feasible and inappropriate.…”
Section: Discussionmentioning
confidence: 99%